Pengaruh Karakeristik Pengawas Internal terhadap Efektivitas Pengendalian Internal Lembaga Perkreditan Desa di Kota Denpasar - Bhuwaneswari, Anak Agung Ayu Mas; Damayanthi, Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p06, 2018)
Internal Controller LPD has an important role in the effectiveness of internal control. This study has aims to obtain empirical evidence on the influence of independence, motivation, professional expertise, education level, and internal supervisor's work experience on the effectiveness of internal control of rural institutions in Denpasar City. This research was conducted at Lembaga Perkreditan Desa in Denpasar City.Sample determination method used is the saturated sample. The sample in this research is 30 LPD with 70 respondents.The data were collected by questionnaire method. Technique analysis data that used is the multiple linear regression test. Based on the result of the research, it is known that the motivation, the level of education and work experience of internal supervisors influence the effectiveness of internal control, while the independence and professional expertise have no effect on the effectiveness of internal control. Keyword: Effectiveness of internal control